Chemical weathering rate, denudation rate, and atmospheric and soil CO2 consumption of Parana flood basalts in Sao Paulo State, Brazil - Conceição, Fabiano Tomazini da [UNESP]; Santos, Carolina Mathias dos [UNESP]; Sardinha, Diego de Souza; Beltran Navarro, Guillermo Rafael [UNESP]; Godoy, Leticia Hirata [UNESP] (Elsevier B.V., 2015)
The chemical weathering rate and atmospheric/soil CO2 consumption of Parana flood basalts in the Preto Stream basin, Sao Paulo State, Brazil, were evaluated using major elements as natural tracers. Surface and rain water samples were collected in 2006, and analyses were performed to assess pH, temperature, dissolved oxygen (DO), electrical conductivity (EC) and total dissolved solids (TDS), including SO42-, NO3-, PO43-, HCO3-, Cl-, SiO2, Ca2+, Mg2+, Na+ and K+. Fresh rocks and C horizon samples were also collected, taking into account their geological context, abundance and spatial distribution, to analyze major elements and mineralogy. The Preto Stream, downstream from the city of Ribeirao Preto, receives several elements/compounds as a result of anthropogenic activities, with only sulfate yielding negative flux values. The negative flux of SO42- can be attributed to atmospheric loading that is mainly related to anthropogenic inputs. After corrections were made for atmospheric inputs, the riverine transport of dissolved material was found to be 30 t km(-2) y(-1), with the majority of the dissolved material transported during the summer (wet) months. The chemical weathering rate and atmospheric/soil CO2 consumption were 6 m/Ma and 0.4 106 mol km(-2) y(-1), respectively. The chemical weathering rate falls within the lower range of Parana flood basalt denudation rates between 135 and 35 Ma previously inferred from chronological studies. This comparison suggests that rates of basalt weathering in Brazil's presentday tropical climate differ by at most one order of magnitude from those prevalent at the time of hothouse Earth. The main weathering process is the monosiallitization of anorthoclase, augite, anorthite and microcline. Magnetite is not weathered and thus remains in the soil profile. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Landscape evolution; Chemical weathering rate; Anthropogenic influence; Atmospheric/soil CO2; Watershed; Denudation rate